Evaluation of cut rose varieties for commercial cultivation under humid tropics of Kerala - Philip, Priya; Sankar, Mini; Sreelatha, U.; Minimol, J.S.; Anupama, T. V. (Journal of Tropical Agriculture, 2020)
A study was conducted at Department of Floriculture and Landscaping, College of Horticulture, Vellanikkara, to evaluate the performance of cut flower rose varieties and to select suitable varieties for commercial cultivation in Kerala. Three IIHR varieties viz., Arka Ivory, Arka Pride, and Arka Swadesh, and seven exotic rose varieties viz., Gold Strike, Noblesse, Revival, Taj Mahal, Corvette, Emma and Peach Avalanche were selected for the study. The varieties varied significantly with respect to various vegetative and floral parameters. The variety Taj Mahal was superior with respect to plant height (52.83 cm). Highest number of flowers were recorded in variety Revival (12.45) which was on par with Arka Ivory (11.38), Arka Swadesh (10.10) and Peach Avalanche (9.87). The variety Taj Mahal had highest number of petals (79.54). Vase life was highest for the varieties Revival (4.83 days), Taj Mahal (4.75 days) and Noblesse (4.75 days). The genetic estimates of heritability (%) and genetic advance (%) were found to be high for the characters fresh weight of flower, number of petals per flower and vase life, indicating that the expression of these characters were due to additive gene action. Varieties Taj Mahal and Noblesse, which were superior with respect to these characters, could be selected for further breeding programme.